2017
DOI: 10.1038/srep40687
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic Control of Heart Rhythm by Selective Stimulation of Cardiomyocytes Derived from Pnmt+ Cells in Murine Heart

Abstract: In the present study, channelrhodopsin 2 (ChR2) was specifically introduced into murine cells expressing the Phenylethanolamine n-methyltransferase (Pnmt) gene, which encodes for the enzyme responsible for conversion of noradrenaline to adrenaline. The new murine model enabled the identification of a distinctive class of Pnmt-expressing neuroendocrine cells and their descendants (i.e. Pnmt+ cell derived cells) within the heart. Here, we show that Pnmt+ cells predominantly localized to the left side of the adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(92 citation statements)
references
References 23 publications
6
86
0
Order By: Relevance
“…In the past decade, there has been explosive growth in the use of optogenetics to study the mouse nervous system in vivo (Deisseroth, 2015). Optogenetic methodology is finding increasing use in cell biology (Grusch et al, 2014;Kim et al, 2016), and further advances in technology should enable the use of optogenetics in investigation of aspects of the cardiovascular system in model systems in vivo (Reade et al, 2017;Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, there has been explosive growth in the use of optogenetics to study the mouse nervous system in vivo (Deisseroth, 2015). Optogenetic methodology is finding increasing use in cell biology (Grusch et al, 2014;Kim et al, 2016), and further advances in technology should enable the use of optogenetics in investigation of aspects of the cardiovascular system in model systems in vivo (Reade et al, 2017;Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…35 Their group have further evaluated the neural axis in the murine heart by identifying and stimulating a subpopulation of cardiomyocytes that bear the phenylethanolamine n-methyltransferase gene, which encodes the enzyme that converts norepinephrine to epinephrine, to exert control on heart rhythm through the use of optogenetics. 106 Wengrowski et al have shown photoactivation of cardiac sympathetic nerves affects cardiac electrical properties to increase heart rate along with cardiac contractile force (Figure 8). 97 To study the effects of vagal tone on exercise capacity, Machhada et al utilized a viral vector system to target neurons in the rat brainstem dorsal ventral motor nucleus, the main vagal nucleus in the central nervous system, with channelrhodopsin ChIEF.…”
Section: Introductionmentioning
confidence: 99%
“…First, cardiac patches should be fabricated with the appropriate dimensions, shape and cell contents for optimal repairing efficacy . Second, given that contractile force and beating frequency have been shown to be a good indicator whether postimplantation integration between the engineered tissue and the patient's heart is likely, the contractile forces and frequencies should be evaluated to ensure proper cardiac function upon integration with the damaged heart . Third, given that the intrinsic mechanical properties of the engineered cardiac tissues can be used to predict whether the tissues can sustain the stress during heart contraction during the implant‐heart integration process, the parameters such as elastic modulus, viscosity, shear modulus, bulk modulus, and dynamic stress distribution should be assessed to verify structural integrity …”
Section: Introductionmentioning
confidence: 99%